Chinese Cultural Identity Represented in Crazy Rich Asian Novel by Kevin Kwan - Theresa Wella Hanggraeni (Jurnal Bahasa, Sastra, dan Studi Amerika, 2025)
This research analyzes Chinese cultural identity represented in Crazy Rich Asian written by Kevin Kwan. It aims to identify the Chinese cultural signs and analyze the representation of Chinese cultural signs in representing Chinese cultural identity in the novel. This research employs semiotic approach by C. S. Peirce in representing Chinese cultural identity. As taking Crazy Rich Asian novel as the main source of data, the data taken is in the form of words, phrases, and sentences in the novel. The collected data is analyzed to identify the Chinese cultural signs and their representation. The results of this research show that there are cultural signs namely language used, body language, and family as Chinese cultural signs in the novel. These signs are identified based on legisign. The representation of Chinese cultural signs is examined by seeing the relationship between the sign and its object in three different perspectives including the similarities (icon), the real cause-effect (index), and the general rules (symbol). The results of their representation show Chinese tradition, terms, history and environment.